Assessing the medical workforces perceived barriers to the prescription of risk‐reducing medication for women at high‐risk of breast cancer. Issue 1 (7th December 2018) - Sutherland, Sarah; Meiser, Bettina; Kaur, Rajneesh; Mitchell, Gillian; Kirk, Judy; Peate, Michelle; Tim Wong, W.K.; Goodwin, Annabel
Abstract: This study aims to determine the attitudes and barriers of Australian oncology health professionals towards using tamoxifen as a breast cancer risk‐reducing medication (RRM). Our target group was health professionals involved in breast cancer risk assessment or treatment. Members of relevant medical organizations in Australia and New Zealand were invited to participate in a web‐based survey assessing: their attitudes towards tamoxifen as a RRM; which health professionals they felt were responsible for initiating and monitoring women on RRM and their views on workforce issues related to RRM prescription. There were 100 respondents, including 33 genetic health professionals, 32 medical oncologists and 20 surgeons. Respondents perceived tamoxifen to be effective as a RRM (99%). However, only 41% of prescribing health professionals (n = 64) had ever prescribed tamoxifen as a RRM. Overall, survey respondents felt that the initiation of RRM was the role of specialists. Assessing a patient's risk of breast cancer was reported to be the role of cancer geneticists/familial cancer clinicians (74%) and medical oncologists (66%). Discussion about the use of RRM was reported to be the role of these same groups (84% and 85% respectively). Medical oncologists (83%) and breast physicians (70%) were most frequently considered to be responsible for initiating the prescription and monitoring women once commenced on RRM (72% and 71% respectively). Oncology health professionals express confidence in the effectiveness of tamoxifen as a RRM despite reporting low prescription rates. Findings demonstrate that these oncology health professionals felt that initiation of RRM was the role of cancer specialists, despite preventative medicine being seen as a primary care activity. If uptake among at‐risk women increases, this will put a significant burden on cancer services and GPs will need to take on a greater role in the delivery of RRM.